Suicidality, self-stigma, social anxiety and personality traits in stabilized schizophrenia patients - a cross-sectional study - Vrbova, Kristyna; Prasko, Jan; Ociskova, Marie; Holubova, Michaela; Kantor, Krystof; Kolek, Antonin; Grambal, Aleš; Slepecky, Milos (Neuropsychiatric disease and treatment, 2018)
BACKGROUND AND AIM: Patients who have schizophrenia are more prone to suicidal behavior than the general population. This study aimed to find connections between suicidality and self-stigma, hope, and personality traits in patients with schizophrenia. METHODS: Forty-eight stabilized outpatients with schizophrenia attended this cross-sectional study. Patients were diagnosed by the Mini International Neuropsychiatric Interview (MINI) using the ICD-10 research diagnostic criteria. The assessments included Positive and Negative Syndrome Scale, objective and subjective Clinical Global Impression, Liebowitz Social Anxiety Scale, Beck Depression Inventory-second edition, Internalized Stigma of Mental Illness, the Temperament and Character Inventory, and Adult Dispositional Hope Scale. RESULTS: The individual rate of suicidality (suicidal index from MINI) strongly positively correlated with self-stigma, level of depression, social anxiety, and harm-avoidance, and negatively correlated with hope, self-directedness, and stigma resistance. CONCLUSION: Individuals with additional symptoms of depression, social anxiety, trait-like anxiety, and self-stigma should be carefully monitored for suicidal ideation. On the opposite side, patients with sufficient hope, self-esteem, and goal-directed attitudes are less likely to have suicidal thoughts and may potentially be role models in group rehabilitation programs, motivating more distressed colleagues and showing them ways to cope.
Keywords: suicidality; hope; self-stigma; positive and negative symptoms; personality traits; schizophrenia; social anxiety